The high cost of healing and teaching: a cross-sectional survey of burnout among academic physicians in Nigeria - Kehinde Sunday Oluwadiya; Anthony A. Olasinde; Adekunle Olatayo Adeoti; Oyewole Adeoye; Ibironke Omowunmi Oluwadiya; Innih Asuekome Kadiri (BMC, 2023)
Abstract Background Globally, the medical and teaching professions are two major professions with the highest prevalence of burnout, and academic physicians bestride the two professions. This study investigated the prevalence and associated factors of burnout among academic physicians working in tertiary hospitals in Nigeria. Methodology This was a self-administered online survey. Burnout was measured using the Maslach Burnout Inventory for Educators (MBI-ES) on Google Form and sent to 256 academic physicians in tertiary hospitals across Nigeria using the WhatsApp broadcast feature. MBI-ES was categorized into two categories (Burnout and No Burnout), and binary logistic regression was used to test the influence of 13 predictors on the three dimensions of MBI-ES as well as MBI in its entirety. Findings A total of 155 academic physicians responded, resulting in a response rate of 60.5%. There were 121 (80.7%) males and 29 (19.3%) females (five cases respondents omitted this detail). Eighty-seven respondents exhibited moderate to high burnout in at least one of the dimensions of the MBI, translating to a prevalence rate of 57.7% in our study. Five variables, number of peer reviewed articles published, hours of weekly teaching, enjoyment of academic writing, apathy to teaching and religion were all significantly associated with burnout. Moderate to high emotional exhaustion was reported by 30.8% (45 respondents), moderate to high depersonalization by 5.5% (8 respondents),, and low to moderate personal accomplishment by 43.5% (67 respondents).Eight variables: religion, geopolitical zone of practice, enjoyment of academic writing, apathy toward teaching, university ownership, number of published peer-reviewed articles, salary, and supplementary income were significantly associated with emotional exhaustion, while the number of weeks spent teaching in a year and teaching hours/week were significantly associated with depersonalization and personal accomplishment, respectively. Age (OR 1.302, CI 1.080-1.570), Teaching hours/week (OR 0.924, CI 0.854-0.999), Salary (OR 0.996, CI 0.993-1.0), and supplementary salary (OR 0.996, CI 0.993-0.999) were found to significantly predict emotional exhaustion. Conclusion The study reveals a high prevalence of burnout (57.7%) among academic physicians in Nigeria, highlighting an urgent need for targeted interventions and policy changes. Given the significant role these professionals play in healthcare and medical education, immediate action is essential to address this issue. Future research should focus on evaluating the effectiveness of preventive measures and exploring the long-term impacts of burnout.